Labour market trajectories, social protection and the green transition in France and Viet Nam - Anil Duman; Sevane Ananian (International Labour Organization (ILO), 2024)
This study investigates labour market transitions to green occupations in France (2017-2021) and Viet Nam (2021-2022) using the longitudinal dimension of labour force surveys in the two countries. According to a task-based definition of green jobs derived from the ISCO-08 classification, our findings show that 21.5 per cent and 15 per cent of workers in France and Viet Nam, respectively, are employed in green jobs. In particular, education appears to have a substantial impact on the transition to green occupations, suggesting that investment in skills may facilitate green transitions in the labour market. Moreover, women are less likely to transition to green jobs than men. Finally, our findings highlight the role of social protection systems, in particular unemployment insurance, in supporting green transitions in the labour market.
Keywords: 330; Labor market; Environmental occupations; Social security; Qualification; Gender; France; Vietnam; Arbeitsmarkt; Umweltberufe; Soziale Sicherheit; Qualifikation; Geschlecht; Frankreich; Vietnam